Effectiveness Of Therapeutic Ultrasound With And Without Ketoprofen Gel Among The Patients Ofnon-Specific Low BackPain - Fahad Tanveer; Sohail Safdar; Adnan Qamar (ziauddin University, 2024)
Background: Lower spinal back pain, a very common everyday problem, experienced by most people in their life, is usually nonspecific low back pain and varies with changes in posture and activity. It is also called mechanical low back pain. Objective: The objective of this study was to examine the effectiveness of therapeutic ultrasound with and without ketoprofen gel on pain and disability in patients with nonspecific low back pain. Methods: The study design was randomized clinical trial, conducted at MadinahTeaching Hospital and Sugraha trust hospital Faisalabad. This study included males and females between ages 20 to 35. A convenient sampling technique was applied, as patients who were visiting the physiotherapy department during months of Febraury-June 2016 were considered. Signed consent forms and the privacy of patients was taken into consideration. Two groups were made; Group A received ultrasound with Ketoprofen gel and strengthening and stretching exercises whereas Group B received ultrasound with Aqua sonic gel and strengthening and stretching exercises. Total treatment sessions were over a period of 10 consecutive days. The pain intensity was measured by visual analogue scale (VAS) and functional level was measured by Oswestry Disability Questionnaire(ODQ) before, in the middle and at the end of the treatment. Results: There was a significant difference before and after treatment in pain intensity between ketoprufen gel (3.07±0.77 and p=0.000) and aqua sonic gel (5.08±0.85 and p=0.06). There was a reduction in disability level after the treatment in both groups but greater improvement was achieved by Ketoprofen gel as compared to aqua sonic gel. Conclusion: Therapeutic ultrasound with ketoprofen gel along with stretching and strengthening exercises is more effective than the aqua sonic gel ultrasound in the management of non-specific lower lumbar back pain. Key Words: ketoprufen, therapeutic ultrasound, nonspecific low back pain